The future of the AFP's defense technology acquisition through scenario planning - Guevarra, Eric D.
Modernization of the armed forces became apparent after the termination of the RP-US bases agreement in 1992. The Armed Forces of the Philippines Modernization Program Management Office was activated by virtue of Congress passed Republic Act Number 7898 in 1995, otherwise known as the AFP Modernization Act. To operationalize this Act, a 15 year planning document was formulated. During the 15 year implementation, the bulk of the fund was used for acquisition of defense equipment which amounts to 26.6 billion or a 93.90 percent share of the total fund. The remaining funds were used for the other components of the modernization program. A total of 42 projects from the Army, Navy and Air Force have been completed out of the 92 projects, while the remaining ongoing projects are in the various stages of the acquisition process. Stumbling blocks hounded the program as external and internal issues abound during the said implementation. Among this were : Limited period of implementation, uncertainty in the availability of funds, One Fund concept, cumbersome procurement policies and procedures and complex acquisition structure, organizational concerns, inability to respond/adapt to issues and concerns identified, absence of institutional memory and changing the rules mid-game. A review of literature further revealed that, it does not have the National Defense Program Guidelines similar to that Japan. It lacked the extensive ownership of military technological capability that made it difficult to formulate a defense policy as patterned from Taiwan. It further stated in the article that the formulation of defense policy is greatly influenced by objective environmental factors which include the relationship between the ally and the potential adversary, as well as the organizations changing roles. The method used in analyzing and coming up with recommendation and conclusion is Scenario Building. Scenario planning, also called scenario thinking or scenario analysis is a strategic planning method that some organizations use to make flexible long-term plans. It is in large part an adaptation and generalization of classic methods used by military intelligence. The analysis followed the 10 steps of scenario building. The author came up with a process based from the on the scenario building and technology acquisition process framework with a recommended model to serve as guide in the acquisition process. In Conclusion, 3 scenarios evolved namely; Scenario 1 : "Star Wars I", Scenario 2 : "Newport City III", Scenario 3 : "Bloody Sunday II", Scenario building is a powerful tool in forecasting. It is a promising tool for strategy formulation. The scenarios that have been formulated provide us with a glimpse of the future. With another probable 15 year extension of the modernization program, it is with high hope that the organization will fulfill its vision of becoming a modern, responsive and a potent force to be reckoned with.